Computed Tomography-Based Body Composition is Related to Perioperative Morbidity in Older Lung Transplant Recipients - Kifjak, Daria; Prosch, Helmut; Schwarz, Stefan; Jaksch, Peter; Weber, Michael; Hoetzenecker, Konrad; Schweiger, Thomas (The Thoracic and Cardiovascular Surgeon, 2024)
Background In older patients, a limited physical reserve is considered a contraindication for lung transplantation (LTx). Herein, we aimed to establish a computed tomography (CT)-based quantification of physical reserve in older patients scheduled for transplantation.Methods This retrospective study included patients older than 60 years who received LTx. Semiautomatic measurements of the mediastinal fat area and the dorsal muscle group area in pretransplantation CT scans were performed, and normalized data were correlated with clinical parameters.Results Patients (n = 108) were assigned into three groups (Musclehighfatlow [n = 25], Musclelowfathigh [n = 24], and other combinations [n = 59]). The Musclelowfathigh group had a significantly increased risk of wound infections (p = 0.002) and tracheostomy (p = 0.001) compared with Musclehighfatlow patients. The median length of intensive care unit stay (25 vs. 3.5 days; p = 0.002) and the median length of hospital stay (44 vs. 22.5 days; p = 0.013) post-LTx were significantly prolonged in the Musclelowfathigh group. Significantly more patients in this group had a prolonged ventilation time (11 vs. 0; p < 0.001).Conclusion Body composition parameters determined in pretransplant chest CT scans in older LTx candidates might aid in identifying high-risk patients with a worse perioperative outcome after LTx.
Keywords: lung transplantation; body composition; biological age; frailty; older patients